PENGARUH PANDEMI COVID-19 TERHADAP PENDAPATAN DI PT JASA MARGA Tbk - Ariska Puji Astuti (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2021)
ABSTRACT The research to learn about the covid-19 known effects covid-19 regarding revenue in Jasa Marga. The research method used was quantitative study method. Data and information procedures use literature and survey study methods. The data analysis techniques used deductive analysis normality tests, simple linear regression and testing. The data used is secondary data of the income statement and the volume of toll vehicles from 2016-2020. Pearson product correlation attained 0.970 means to show the relationship rate between the two variables very strong range. The coefficient value of determinations is 94.1% means that the income in Jasa Marga 2016-2020 is affected by covid-19 pandemic of 94.1% and 5.9% affected by other factors That the authors didn't study. Hypothetical testing using tests with its significant value is thitung 6.913 and ttable 3.182 then was rejected and received. This explains that there are significant effects of the covid-19 pandemic variable on income. Advice given this research is that Jasa Marga companies can make performance system especially regarding risk management which is even better so that it can minimize the risk or problems that will occur in the future such as a decrease in vehicle volume and a decrease in income. Keywords: Covid-19 Pandemic, Revenue, Jasa marga